Plyometric Training Depth Jump and Plyometric Multiple Box-To-Box Squat Jump for Increasing Movement Speed and Explosive Power of Athletes' Lemb Muscles - Muhammad Muhammad; M. Yahya; Muhammad Syahwal; M.Arif Fadhillah (LPPM Universitas PGRI Sumatera Barat, 2024)
Plyometric training is an exercise that relies on maximum muscle contraction which will increase if the active muscles are stretched appropriately and there is continuous (continued) movement. The aim of this research is to determine: 1) the effect of plyometrics depth jumps training on increasing movement speed and explosive power of athletes' leg muscles, 2) the effect of multiple box-to-box squat jumps plyometrics training on increasing movement speed and explosive power of athletes' leg muscles , 3) differences in the results of plyometrics depth jump and plyometrics multiple box-to-box squat jump training on increasing movement speed and explosive power in athletes' leg muscles. The population of this study were Physical Education students Class of 2020, Jabal Ghafur University, Sigli Pidie Regency aged 20-24 years with a sample size of 30 people who were divided into 3 groups (depth jump multiple box-to-box squat jump, and control) and each The group consists of 10 people. The method in this analysis uses comparative statistical methods with the Multivariate Analysis of Variance (Manova) test, while the data collection process is carried out by carrying out movement speed measurement tests using the 30 meter running test and measuring muscle explosive power. legs using the vertical jump test. Results: (1) Plyometric depth jump training has a significant effect on increasing movement speed and explosive power of athletes' limb muscles. The average change in movement speed was 0.44 m/sec or an increase of 7.29% and the average change in explosive power was 10.50 watts or an increase of 11.62%. (2) Multiple box-to-box squat jump plyometric training has a significant effect on increasing movement speed and leg muscle explosive power. The average change in movement speed was 0.98 m/sec or an increase of 15.54% and the average change in explosive power was 17.05 watts or an increase of 20.37%. (3) There is a significant difference between the results of plyometric depth jump and plyometric multiple box-to-box squat jump training on increasing movement speed and explosive power in athletes' leg muscles.